Identifying Factors Associated with the Efficacy of Lasmiditan 50 mg as an Acute Treatment for Migraine Attacks Under Various Dosing Conditions in Real-World Clinical Practice - Takafumi Tanei; Shun Yamamoto; Satoshi Maesawa; Yusuke Nishimura; Tomotaka Ishizaki; Yoshitaka Nagashima; Yoshiki Ito; Miki Hashida; Takahiro Suzuki; Hajime Hamasaki; Toshihiko Wakabayashi; Ryuta Saito (Neurology International)
Background/Objectives: Lasmiditan is a newly developed drug for the acute treatment of migraine attacks, but factors associated with its efficacy remain unclear. This study aimed to confirm the efficacy of lasmiditan started at 50 mg under various dosing conditions and identify factors associated with its efficacy. Methods: There are four reasons for prescribing lasmiditan: as an add-on to triptan, if triptan is ineffective, if triptan produces side effects, and when triptan is contraindicated. Lasmiditan was administered at a dose of 50 mg. The efficacy of lasmiditan was defined as the disappearance of headache or a 50% or greater reduction in headache intensity within two hours after dosing. This study included 108 patients with migraines who took lasmiditan. Results: The results for efficacy and the side effects of lasmiditan were as follows: effective without side effects (22), effective with mild side effects (32), ineffective (14), and severe side effects (40). The efficacy rate of lasmiditan 50 mg was 50.0% (54/108). The following factors were found to be associated with lasmiditan’s efficacy: sex, migraine classification, calcium channel blockers, and anti-calcitonin gene-related peptide monoclonal antibody (CGRP-mAb) treatment. The overall incidence of side effects was 66.7%, and the dropout rate was 37.0%. Somnolence was more prevalent in the effective group, and other side effects were more prevalent in patients who dropped out due to the side effects of lasmiditan. Conclusions: Lasmiditan is likely to be effective in males with severe migraine classification and receiving CGRP-mAb treatment. If mild somnolence is a side effect, the drug can be continued and may be effective.